Dorsal-ventral midline signaling in the developing Drosophila eye. - Sato, A.; Tomlinson, A. (Development, 2007)
Boundaries between different cell types play key roles in many developmental patterning processes. They can be established by various mechanisms, and signaling between the different cell types can occur in a number of ways. One mechanism of crossboundary signaling is controlled by the Notch (N)-modifying protein Fringe (Fng). At the Drosophila wing dorsal-ventral (D-V) border, the mechanism by which an Fng(+)-Fng(-) interface controls local N activation has been well characterized. A similar N-activating Fng(+)-Fng(-) interface has also been described at the D-V border of the fly eye, but the mechanisms that establish and regulate it are different from those in the wing. Here we describe the ventral role of the Sloppy-paired (Slp) transcription factor, and its interactions with dorsally expressed Iroquois (Iro) transcription factors in the regulation of signaling about the Fng(+)-Fng(-) interface in the developing eye. The two transcription factors are mutually repressive and initially abut at the D-V midline. However, N signaling at the interface downregulates Slp expression, and a gap opens between the two expression domains in which Serrate (Ser, an N ligand) is upregulated.